Challenges for developing Forest Stewardship Council certification for ecosystem services: How to enhance local adoption? - Savilaakso, S.; Guariguata, Manuel R. (Elsevier, 2017)
The rise of ecosystem services (ES) as a conservation and management tool has changed the way forests are conceived, but so far its translation into management actions has been limited. In this paper, we discuss the development of certification of forest ecosystem services (FES) from the perspective of those implementing it at the local level. We focus on the lessons that emerged from applying the Forest Stewardship Council (FSC) certification framework at selected sites in Chile, Indonesia, Nepal and Vietnam. Our results indicate a clear relationship between local and global levels in the development of FSC FES certification. Although the FSC already had a broad vision of ES, it was only through local-level learning within a specific pilot experiment that the vision evolved and resulted in more formal FES certification becoming part of FSC forest management certification. We also found that those sites where participatory approaches to management and decision-making were applied could work with an undefined vision of the future system, and still successfully design and implement management activities. However, overall the lack of specific vision and detailed information about future FES certification was problematic in attracting market interest in FSC certified ES.